High-pressure melanocratic rocks of Anrakhai sialic massif (Southern Kazakhstan): the features of mineral, chemical compositions and metamorphism paths - A. V. Pilitsyna; A. A. Tretyakov; K. E. Degtyarev; E. V. Kovalchuk (Известия высших учебных заведений: Геология и разведка, 2015)
In the structure of Anrakhai massif of Chu-Ili region (Southern Kazakhstan) metamoiphic formations of high-pressure conditions derivation (under eclogite facies field) were identified; the rocks are represented by eclogites and garnet clinopiroxenites. Investigation of mineral and chemical compositions of melanocratic high-pressure varieties as well as detailed petrographic and geological studies allowed characterizing P-T parameters of the metamorphic rocks formation (P 1,6-2,1 GPa; Г750-840°C), determining presumed protolith composition for them, that represented evidently the fragment of differentiated complex of mafic-ultramafic compositions, located within the continental crust prior metamorphism.